History of Medieaval Hindu India : Volume 2: Early History of Rajputs (750 to 1000 A.D.) - Vaidya, C.V. (Brill | Manohar Publishers & Distributors, 2024)
Rajputs are a warrior caste who established major kingdoms in Northern India in the early medieval times. During the Sultanate and Mughal rule, Rajputs played a key role in kingship. This book is the second volume of History of Medieaval Hindu India's three-volume series, which covers the history of the Rajput community starting from ad 750 till ad 1000 when the Turkish invasions began. The book has three parts. The first part starts with the genealogical origins of the Rajput clan, especially their foreign origins propounded by contemporary scholars. The second part covers the historical profile of kingdoms in Northern India and Deccan regions such as Chahamanas, Chandellas, Palas, Rashtrakutas, and others. This book also contains the description of Rajputs made by the Arab chroniclers who visited India during the said period. The concluding part deals with the language, cultural, religious, political, civil, and administrative roles and responsibilities of Rajputs in the medieval period.